Environmental Risk Management of Flyover Construction Using Fault Tree Analysis and 4T Mitigation - Fahara, Adista; Rachmansyah, Arief; Eko Andi Suryo (Rekayasa Sipil, 2026)
Flyover construction in urban areas can pose environmental risks, particularly air pollution and traffic congestion, that may adversely affect public health and vehicle operating costs. This study aims to analyze environmental risks arising during the construction phase of the Aloha Flyover Project and to formulate appropriate mitigation strategies. Data were collected through field surveys and structured interviews with 50 respondents at five locations with high traffic intensity. Risk probability and impact were assessed using the Severity Index and a probability-impact matrix. High-priority risks were further examined using Fault Tree Analysis (FTA) and Minimum Cut Set analysis to identify dominant root causes. Risk mitigation strategies were developed based on the 4T framework: Terminate, Treat, Transfer, and Tolerate. The results indicate that increased vehicle operating costs and respiratory health disturbances constitute the most significant risks. These risks are primarily influenced by stop-and-go traffic conditions, elevated engine temperatures, prolonged exposure to vehicle emissions, and construction-generated dust. The findings demonstrate that the combined application of the Treat and Terminate strategies is the most effective for reducing risk levels. In contrast, the Transfer and Tolerate strategies serve as complementary measures. This study confirms that integrating FTA with the 4T approach provides a systematic and practical framework for environmental risk management in urban flyover construction projects, supporting sustainable infrastructure development.